2018
DOI: 10.1016/j.cmet.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination of ABCE1 by NOT4 in Response to Mitochondrial Damage Links Co-translational Quality Control to PINK1-Directed Mitophagy

Abstract: Translation of mRNAs is tightly regulated and constantly surveyed for errors. Aberrant translation can trigger co-translational protein and RNA quality control processes, impairments of which cause neurodegeneration by still poorly understood mechanism(s). Here we show that quality control of translation of mitochondrial outer membrane (MOM)-localized mRNA intersects with the turnover of damaged mitochondria, both orchestrated by the mitochondrial kinase PINK1. Mitochondrial damage causes stalled translation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 68 publications
5
77
0
Order By: Relevance
“…Our recent studies revealed that on damaged mitochondria, the recruitment of cotranslational quality control factors Pelo, ABCE1, and NOT4 to stalled ribosomes results in NOT4‐mediated polyubiquitination of ABCE1 and that polyubiquitinated ABCE1 (poly‐Ub‐ABCE1) provides a molecular signal for recruiting autophagy receptors to initiate mitophagy . We provided evidence supporting that the PINK1 pathway is deployed to stimulate translation of nuclear‐encoded respiratory chain (nRCC) mRNAs on mildly damaged mitochondria to promote RC biogenesis and thus mitochondrial repair, revealing a new physiological role of PINK1/Parkin in mitochondrial regulation.…”
Section: Mitophagy and Neurodegenerative Diseasesmentioning
confidence: 85%
See 1 more Smart Citation
“…Our recent studies revealed that on damaged mitochondria, the recruitment of cotranslational quality control factors Pelo, ABCE1, and NOT4 to stalled ribosomes results in NOT4‐mediated polyubiquitination of ABCE1 and that polyubiquitinated ABCE1 (poly‐Ub‐ABCE1) provides a molecular signal for recruiting autophagy receptors to initiate mitophagy . We provided evidence supporting that the PINK1 pathway is deployed to stimulate translation of nuclear‐encoded respiratory chain (nRCC) mRNAs on mildly damaged mitochondria to promote RC biogenesis and thus mitochondrial repair, revealing a new physiological role of PINK1/Parkin in mitochondrial regulation.…”
Section: Mitophagy and Neurodegenerative Diseasesmentioning
confidence: 85%
“…(poly-Ub-ABCE1) provides a molecular signal for recruiting autophagy receptors to initiate mitophagy. 119 We provided evidence supporting that the PINK1 pathway is deployed to stimulate translation of nuclear-encoded respiratory chain (nRCC) mRNAs on mildly damaged mitochondria to promote RC biogenesis and thus mitochondrial repair, revealing a new physiological role of PINK1/ Parkin in mitochondrial regulation. However, for severely damaged mitochondria that are beyond repair, the PINK1 pathway is used to direct their clearance by mitophagy.…”
Section: Pink1 and Parkinmentioning
confidence: 90%
“…Remarkably, OE of co-translational QC factors, with the OE effect verified for certain key factors ( Figure S2D), effectively rescued PINK1 phenotypes in the muscle (Figure 2E Consistent with the co-translational QC genes working in the same pathway as PINK1 to control C-I30-u expression and mitochondrial function, muscle-specific knockdown of UPF3, a key NMD factor (Leeds et al, 1992), was sufficient to phenocopy PINK1. Similarly, musclespecific expression of dominant-negative VCP, a key RQC factor (Brandman et al, 2012), or overexpression of NOT4, a protein implicated in the co-translational QC of C-I30 (Wu et al, 2018), also phenocopied PINK1 ( Figure 1F; S1B, C).…”
Section: Co-translational Qc Pathways Regulate C-i30-u Formationmentioning
confidence: 88%
“…ABCE1 may be part of the translation machinery that senses mitochondrial health. Indeed, metazoan ABCE1 is ubiquitinated under mitochondrial stress (Wu et al, 2018), and at least in yeast cells, WT level of ABCE1 is below the threshold sufficient for complete ribosome recycling (Young et al, 2015). ABCE1 is innately metastable and prone to sequestration by disease-associated aggregates (Olzscha et al, 2011).…”
Section: Linking Mitochondrial Dysfunction With Cte-induced Neurodegementioning
confidence: 99%
“…The cotranslational quality control factors Pelo, ABCE1, and NOT4 are recruited to the mRNA‐ribonucleoprotein complex, and ABCE1 is ubiquitinated by NOT4. As a result, the poly‐Ub‐ABCE1 recruits the autophagy receptors such as p62, PTEN, and NDP52 to initiate mitophagy . In this issue, Yan Wang and Na Liu at Soochow University and Bingwei Lu reviewed the mechanisms of mitophagy in higher organisms and the roles of mitophagy in the pathogenesis of neurodegenerative diseases .…”
mentioning
confidence: 99%